2014
DOI: 10.1371/journal.pone.0102115
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pleistocene Climatic Changes and Ocean Currents on the Phylogeography of the Southern African Barnacle, Tetraclita serrata (Thoracica; Cirripedia)

Abstract: The evolutionary effects of glacial periods are poorly understood for Southern Hemisphere marine intertidal species, particularly obligatory sessile organisms. We examined this by assessing the phylogeographic patterns of the southern African volcano barnacle, Tetraclita serrata, a dominant species on rocky intertidal shores. Restricted gene flow in some geographical areas was hypothesized based on oceanic circulation patterns and known biogeographic regions. Barnacle population genetic structure was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…This can be particularly pronounced in populations which undergo fluctuations in population sizes, which influences population bottlenecks and even extinctions. In South Africa, reduced gene flow occurs around Cape Point, a biogeographic barrier which separates the west from the south‐west coast, for some species (von der Heyden et al ., ; Muller et al ., ; Reynolds et al ., ). This may well be a factor in separating populations on either side of Cape Point and contribute to reduced levels of genetic diversity for some species.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This can be particularly pronounced in populations which undergo fluctuations in population sizes, which influences population bottlenecks and even extinctions. In South Africa, reduced gene flow occurs around Cape Point, a biogeographic barrier which separates the west from the south‐west coast, for some species (von der Heyden et al ., ; Muller et al ., ; Reynolds et al ., ). This may well be a factor in separating populations on either side of Cape Point and contribute to reduced levels of genetic diversity for some species.…”
Section: Discussionmentioning
confidence: 97%
“…DNA sequence data on 11 intertidal marine species were taken from published works (Neethling et al ., ; Teske et al ., ; von der Heyden et al ., , ; Muller et al ., ; Reynolds et al ., ), as well as unpublished data (Muteveri, ); two new data sets ( Acanthochiton garnoti and Cyclograpsus punctatus ; Appendix S1 in Supporting Information) were generated for this study (Table ; Appendix S1). Sampling sizes for each species and locality are given in Appendix S2.…”
Section: Methodsmentioning
confidence: 99%
“…albicostatus . Species exhibiting pre‐LGM population expansions include tubeworms (Jolly, Viard, Gentil, Thiebaut, & Jollivet, ) and the brown algae Fucus (Hoarau, Coyer, Veldsink, Stam, & Olsen, ) in the Northeast Atlantic, as well as the barnacles Tetraclita serrata (Reynolds, Matthee, & von der Heyden, ) in South African waters and Chthamalus challengeri and Chthamalus moro in the West Pacific (Cheang et al., ; Wu et al., ). By contrast, the sea bass and redlip mullet (Liu, Gao, Wu, & Zhang, ; Liu, Gao, Yokogawa, & Zhang, ), mitten crab (Xu et al., ) and mud crab (He et al., ) exhibit post‐LGM expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Recent phylogeographic work on coastal invertebrate species has led to the discovery of cryptic diversity in poorly dispersing species around the world (e.g., Chan, Tsang & Chu, 2007 ; Hurtado, Lee & Mateos, 2013 ; Radulovici, Sainte-Marie & Dufresne, 2009 ; Santamaria et al, 2017 ; Santamaria et al, 2016 ; Santamaria, Mateos & Hurtado, 2014 ; Santamaria et al, 2013 ; Varela & Haye, 2012 ). In South Africa, cryptic diversity has been reported for several coastal invertebrate taxa ( Evans et al, 2004 ; Mmonwa et al, 2015 ; Reynolds, Matthee & Von der Heyden, 2014 ; Ridgway et al, 2001 ; Teske et al, 2007 ; Zardi et al, 2007 ), including direct-developing crustacean peracarids. Teske et al (2006) reported the presence of multiple deeply-divergent lineages for Exosphaeroma hylecoetes and Iphinoe truncata , with Baldanzi et al (2016) reporting the presence of multiple evolutionary lineages within the amphipod Talorchestia capensis .…”
Section: Introductionmentioning
confidence: 99%